Neuron-specific regulation of class I PI3K catalytic subunits and their dysfunction in brain disorders - Gross, Christina; Bassell, Gary J. (Frontiers in Molecular Neuroscience, 2014)
The PI3K complex plays important roles in virtually all cells of the body. The enzymatic activity of PI3K to phosphorylate phosphoinositides in the membrane is mediated by a group of catalytic and regulatory subunits. Among those, the class I catalytic subunits, p110α, p110β, p110γ and p110δ, have recently drawn attention in the neuroscience field due to their specific dysregulation in diverse brain disorders. While in non-neuronal cells these catalytic subunits may have partially redundant functions, there is increasing evidence that in neurons their roles are more specialized, and confined to distinct receptor-dependent pathways. This review will summarize the emerging role of class I PI3K catalytic subunits in neurotransmitter-regulated neuronal signaling, and their dysfunction in a variety of neurological diseases, including fragile X syndrome, schizophrenia and epilepsy. We will discuss recent literature describing the use of PI3K subunit-selective inhibitors to rescue brain disease-associated phenotypes in in vitro and animal models. These studies give rise to the exciting prospect that these drugs, originally designed for cancer treatment, may be repurposed as therapeutic drugs for brain disorders in the future.